Primary ovarian pregnancy a rare clinical entity: a case report - Yadav, Shweta Tomar; Kaur, Simmanjit; Goyal, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Ovarian pregnancy is a rare form of ectopic pregnancy. It constitutes <3% of all ectopic pregnancies with an incidence ranging from 1:6000 to 1:40000 pregnancies. There has been an increase in the incidence of ovarian pregnancies due to better diagnostic modalities such as transvaginal ultrasonography (TVS) and serum beta-HCG estimation. Though it is usually misdiagnosed as ruptured tubal pregnancy, ruptured haemorrhagic cyst, ruptured corpus luteal cyst, therefore, awareness of this rare condition is important in reducing the associated risk. Hence, we report a case with ectopic ovarian pregnancy managed by conservative surgery at MMIMSR, Mullana, Ambala. Ovarian ectopic pregnancy can be managed by conservative surgeries.